Poxoréu: percursos histórico-políticos - Borges, Pedro Pereira (2012)
The objective of this thesis is to seek the causes of the immobilism of the powerful who settled in municipal administration, as well the causes of the people of Poxoréu conformism. The work can also be used to analyze similar situations in many parts of Brazil, marked by the colonelism or caudillismo. From its connection with the history of Garças and Araguaia region, which had a miner and warrior colonelism, the miner colonelism of Poxoreu is connected to the democratic game created by the municipal elections of 1947 and that had installed in the municipal administration until 2000. The hypothesis that best fits the situation of both region that, throughout the twentieth century, have undergone a process of creating political and social relations similar to the model of Caesarism. The Caesarism seeks solutions to political problems by military actions. At Garças and Araguaia, for example, Colonel José Morbeck had organized the region along these lines, i.e., sharing the organization of all human settlements with their various representatives. In Poxoréu, due to the electoral system introduced in 1947 and renovated in 1965 and also in 1979, the leaders were able to coexist with forms of parliamentary representation, by articulating a balanced policy that pretend to correspond to the interests of the community. The work can be justified because it covers a relatively large period of the Poxoréu s history, while in other Brazilian regions and Mato Grosso were taking important political, economic and social policy, and Poxoréu was not able to adapt after exhaustion of diamond reserves that led to the economic stagnation of the municipality. The methodology used to develop this thesis is historical, but there are others important themes to analyze, such as, for example, the issue of leaders, which appear stronger over all the work. Then, the history of Poxoréu is put within the history of Mato Grosso and Brazil, and also seeks to reconstruct the routes of migrants throughout the twentieth century for the region, and seek, in the armed conflict in the Garças and Araguaia and in the violence inside the miner region, the causes of the immobilism of the powerful and conformism of the people, with the reflections that are still being felt after the first decade of the twenty first century